The effect of corporate governance on financial performance of rural banks in Ghana - Alhassan Musah; Mavis Yaa Adutwumwaa (International Journal of Financial, Accounting, and Management, 2021)
Purpose: The study examined the influence of various corporate governance structures such as board size, board independence, board gender diversity and CEO duality on the financial performance of rural banks in Ghana. Research methodology: The study collected secondary data from the annual report of 30 rural banks for a 10-year period spanning 2010 to 2019. The data was coded into excel and exported into STATA where descriptive statistics, correlation analysis and regression analysis were adopted to answer the research questions. Results: The result shows that there was a positive but statistically insignificant association between CEO duality and ROA and ROE. The study further reveals a positive association between board size and ROA and ROE even though that of ROA was statistically insignificant. Also, board independence was found to be a significant determinant of rural bank financial performance In addition to the above, the study reported a negative association between gender diversity on the boards of the rural bank and ROA and ROE and both associations were statistically significant. Limitations: As a result of the lack of publicly available data on rural banks in Ghana, the study relied on only 30 out of the over 100 rural banks currently operating across the country. Contribution: The result of the study will help the Bank of Ghana and the ARB Apex Bank in their formulation of an appropriate corporate governance framework for rural banks in Ghana and enlighten managers of rural banks on corporate governance structures that enhance their financial performance in Ghana. Keywords: Corporate governance, Rural banks, Return on Assets, Return on Equity, Ghana